Population dynamics of the Mediterranean green crab Carcinus aestuarii Nardo, 1847 (Crustacea: Portunidae) in the Gediz Delta (İzmir Bay, Eastern Aegean Sea) - Tiraşin, Eyüp Mümtaz (Array, 2020)
A total of 6265 Mediterranean green crabs Carcinus aestuarii were sampled from the Gediz Delta in the eastern Aegean Sea (Turkey) during 24 sampling surveys with a 15-day interval from November 2014 to October 2015. The overall ratio of males to females was 1.8:1. Males were predominant in all sampling surveys, except in September 2015. The ranges of total weight (W) and carapace width (CW) for all crabs were 0.19–45.74 g and 8–53 mm. Male crabs were, on average, larger and heavier than females. The W–CW relationships were W=0.0004×CW2.88 for females, and W=0.0003×CW2.96 for males. The estimated von Bertalanffy growth parameters for females were: CW∞=49 mm, K=0.82 year-1 and t0=-0.9 year, and for males CW∞=54 mm, K=0.92 year-1 and t0=-0.96 year. The total mortality rates were 2.25 and 2.27 year-1 for females and males, respectively. The breeding season spans from mid fall to early spring peaking in winter. The recruitment of juveniles to the lagoon happens predominantly in summer. The median size at first maturity was 30.6 mm for females and 41.5 mm for males. The average potential fecundity estimate was 63565±36519 oocytes per female crab while the average realized fecundity was 42810±33310 eggs.